If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -14 + 3 = 4 Reorder the terms: -14 + 3 + 6x = 4 Combine like terms: -14 + 3 = -11 -11 + 6x = 4 Solving -11 + 6x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 6x = 4 + 11 Combine like terms: -11 + 11 = 0 0 + 6x = 4 + 11 6x = 4 + 11 Combine like terms: 4 + 11 = 15 6x = 15 Divide each side by '6'. x = 2.5 Simplifying x = 2.5
| 3x-4=4x+10 | | 6b+2=9-4b | | 3x(5-2x)=x-21 | | lgx=3 | | 6x+4y-5=0 | | k/9-1=10 | | -x^2-2x+1=0 | | x/2+7=11 | | x+(x+6)=60 | | 2(3x+1)-4=16 | | (4x^4)= | | x^3-19x^2+48=0 | | 8a-2=4a-5 | | 5n+3=2n+1 | | 2d-9=-9 | | (x-4)(x^3)= | | 10x-3=3x-1 | | 4(s+1/2)=8(s+3/4) | | t-4=-3t-10 | | 5x+16+10=47 | | 2+2y=-1+3y | | y=1.23x-0.19x^2 | | 5-7m=2-6m | | 6x-7=x-32 | | (x+6)(7x+10)=0 | | 3y^2-8y=2 | | 6-10a=8-9a | | 8-4x=18-5x | | 8b^2-5b=10 | | 4x+23-10=34 | | (3,2),(4,1)= | | p=x^2-4x-8 |